Management of Spontaneous Cornual Heterotopic Pregnancy in Low-Resources Setting: Tata Laksana Kehamilan Heterotopik Kornual Spontan pada Keadaan Sumber Daya Terbatas - Jacklyn Yosefin Gracia Lubis; Yosep Sutandar; Lidya F. Nembo (Indonesian Journal of Obstetrics and Gynecology, 2023)
Objective: To report management of spontaneous cornualheterotopic pregnancy in low-resources setting in EndeDistrict, Flores, East Nusa Tenggara.Methods: Case report.Case: A 34 year old primigravida with history of 8-9 weeksamenorrhea came to Obstetrics ER with chief complaintof vaginal bleeding and lower abdominal pain. Ultrasoundshows intrauterine pregnancy (IUP), an ectopic pregnancy(EP) in right uterine cornu, and free fl uid in hepatorenalspace, splenorenal space, and pouch of douglas suggestingthe occurrence of hemoperitoneum and heterotopicpregnancy. We performed cornual resection by laparotomyand administered progesterone orally before and after thesurgery. Successful outcome was achieved.Discussion: Heterotopic pregnancy (HP) rarely occurs,especially in natural conception. Thus, early diagnosis andtreatment of HP are quite a challenge for physicians especiallyin rural area. Due to the condition of our patient and limitedresources, laparotomy was conducted to remove the EP,rather than laparoscopy despite its advantage to lower riskof IUP abortion. Progesterone was then administered orallyto prevent threatened abortion of the IUP.Conclusion: Despite its challenge in diagnosing andtreating HP, it is a life-threatening condition that requiresaccurate and prompt treatment. The treatment goal is toremove the EP and preserve the IUP. Treatment of choiceshould be decided by takeing the patient’s condition andavailability of resources into account. Surgical along withadministration of progesterone before and after the surgerywould likely improve the outcome of the patient and theintrauterine pregnancy.Keywords: cornual resection, heterotopic pregnancy,laparotomy, low-resources setting, progesterone.AbstrakTujuan: Untuk membahas tentang penatalaksanaankehamilan heterotopik kornu spontan di daerah dengansumber daya rendah khususnya di Kabupaten Ende, Flores,Nusa Tenggara Timur.Metode: Laporan KasusKasus: Seorang perempuan primigravida usia 34 tahundengan riwayat amenore minggu ke-8 dan 9 datang keIGD Obgyn dengan perdarahan pervaginam dan nyeriperut bagian bawah. Temuan USG menunjukkan kehamilanintrauterin (KIU), kehamilan ektopik (KE) di tanduk rahimkanan, dan cairan bebas di ruang hepato-renal, splenorenal,dan cavum douglas. Hal ini menunjukkan terjadinyahemoperitoneum dan kehamilan heterotopik. Reseksikornu dengan laparotomi dilakukan dan pasien diberikanprogesteron secara oral sebelum dan setelah operasi.Luaran baik berhasil dicapai.Diskusi: Kehamilan heterotopik jarang terjadi, terutamapada konsepsi alami. Sehingga diagnosis dan tata laksanaKH sejak dini menjadi tantangan bagi para dokter, terutamadi daerah terpencil Karena kondisi pasien dan sumber daya,laparotomi dilakukan untuk mengangkat KE, daripadalaparoskopi meskipun keuntungannya dalam menurunkanrisiko keguguran KIU. Progesteron kemudian diberikansecara oral untuk mencegah terjadinya keguguran terancamdari KIU.Kesimpulan: Terlepas dari tantangan untuk diagnosisdan tatalaksananya, KH adalah kondisi yang mengancamjiwa yang membutuhkan penanganan yang akurat dansegera. Tujuan tatalaksananya adalah untuk mengangkatKE dan mempertahankan KIU. Pilihan tata laksana harusdiputuskan dengan mempertimbangkan kondisi pasien danketersediaan sumber daya. Pendekatan bedah dan obatdengan progesteron yang diberikan sebelum dan sesudahoperasi akan meningkatkan kemungkinan luaran pasien dankehamilan intrauterine yang baik.Kata kunci: kehamilan, heterotopik, laparotomi,progesteron,reseksi kornual, sumber daya rendah.